Analysis of export restraints disputes as trade policy within the GATT and WTO regime (2018)
Since GATT and WTO foundation, some disputes have occurred between their full member regarding the adoption of export restrictions, which has generated a neo-protectionism or “reverse protectionism”, which is not yet properly regulated within the multilateral trading system. This article aims to present an analysis of the export restrictions in international trade. For this, all the disputes raised to date on tariff measures and non-tariff measures applied to the export of goods under the GATT and WTO regime are identified. Therefore, we concluded that it is necessary for the WTO to develop trade policies that properly regulate export restrictions in international trade. Keywords: Reverse Protectionism, Neo-Protectionism, Export Restraint, Multilateral Trading System, GATT, WTO.